PENGARUH FINANCIAL DISTRESS DAN LEVERAGE TERHADAP KONSERVATISME AKUNTANSI - Wulan Riyadi (EKBIS (Ekonomi & Bisnis), 2022)
The more intense competition in the business world, the companies are competing to get investors by applying accounting conservatism and it is believed that it can save a company from bankruptcy. However, its application will make the company's financial statements unnatural so that the company is faced with the consideration of presenting quality financial reports. This study aims to determine the effect of financial distress and leverage on accounting conservatism in transportation sub-sector service companies listed on the Indonesia Stock Exchange for the 2015-2019 period. The analytical method used is descriptive analysis method and verification. The sample selection in this study using purposive sampling method. The population in this study were 46 companies and the sample was 16 service companies in the transportation sub-sector in the 2015-2019 period. The analytical tool used in this research is multiple linear regression analysis. The partial and simultaneous test results show that financial distress has a significant effect on accounting conservatism and leverage has a significant effect on accounting conservatism.